Combined action of pyronaridine and sulfadoxine/pyrimethamine against Plasmodium berghei ANKA strain in mice - SHI Xiao-hua; SHAO Bao-ruo; YE Xiu-ye (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Pyronaridine, a highly effective antimalarial drug, was synthesized and developed by this institute. In order to test whether the joint blood schizontocidal action of pyronaridine (PND) and 2:1 mixture of sulfadoxine/pyrimethamine (SP) resulted in a potentiation or an additive effect, groups of P berghei ANKA strain-infected mice were treated with various single oral doses of PND and SP. Thin blood smears were made after 72 h and the parasitemia-negative rates were calculated. The ED50 values obtained were plotted in isobolograms. An additive action of this triple combination was demonstrated. Mice were inoculated with P berghei ANKA strain-infected erythrocytes 3 and 2 d after the mice were given a single oral dose of PND 10 mg/kg alone, or combined with SP 3 mg/kg. Thin blood smears made on d 3, 5, 8 and 10 revealed that the parasitemia-positive rates and the duration of residual blood schizontocidal action of PND used alone was similar to that of PND used in combination (P greater than 0.05). Three groups of mice carrying P berghei ANKA strain gametocytes were administered orally with pyrimethamine 0.1 mg/kg, SP 0.3 mg/kg and SP 0.3 mg/kg plus PND 0.5 mg/kg, respectively. Anopheles stephensi were then fed on the mice 2 h after the medication. There resulted no significant differences of gametocytocidal and sporontocidal effects among the 3 groups, since the oocyst-positive rate and the glandpositive rate were similar in these groups.